Pengaruh Pengawasan Disiplin Kerja Terhadap Kinerja Pegawai Pada Lembaga Pemasyarakatan Kelas II A Karawang - Winda Dwi Agustini; Dedi Mulyadi (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The influence of oversight of work discipline on employee performance in class IIA prisons in Karawang. This study aims to analyze the effect of work discipline and supervision on employee performance. The population in this study was collecting data using a questionnaire and analyzed using multiple linear regression. The results of this study indicate that work discipline does not affect performance, supervision does not affect performance. But discipline by each other’s awareness and according to the rules that have been ordered.It is important to note that discipline does not mean a life without flexibility or creativity. Proper flexibility and the ability to adapt to new situations are also part of good discipline. Discipline helps a person maintain a balance between structure and freedom, so that he can achieve goals effectively and efficiently.